Multiple regulation of surface engineering for lithium-rich layered cathode materials via one-step strategy. (1st December 2019) - Jiang, Xia; Wu, Bing; Yang, Xiukang; Xiong, Ke; Liu, Qiwen; Zhang, Yi; Shu, Hongbo; Gao, Ping; Xu, Sheng; Wang, Xianyou
Abstract: The lithium-rich layered oxides have been regarded as one of the most promising cathode materials for high energy lithium-ion batteries, while their commercial applications are still limited by the disadvantages of low initial coulombic efficiency, excessive capacity fading and voltage decay. Herein, a significant strategy has been proposed to combine the advantages of the formation of spinel phase, surface coating and surface treatment via a one-step strategy to improve electrochemical proprieties of lithium-rich cathode materials. The optimized lithium-rich layered particle with a unique spinel@NPPy (naphthalene sulfonic acid-doped polypyrrole) shell exhibits a high initial coulombic efficiency of 92% during the first charge-discharge cycle. Moreover, the as-prepared sample displays excellent cycling performance with a capacity retention of 89% after 200 cycles at 0.5 C, while only 68% for the pristine one. Remarkably, the corresponding voltage decay of the modified material after 200 cycles is only 0.36 V, showing the voltage decay is well suppressed by this multiple regulation method. The impressive electrochemical performances of modified lithium-rich layered cathode material can be ascribed to its special surface engineering based on layered@spinel@NPPy heterostructure, which is conducive to shortening Li-ion diffusion paths, reducing charge transfer impedance and enhancing structural stability.